SARS-CoV-2 variants from COVID-19 positive cases in the Free State province, South Africa from July 2020 to December 2021 - Mwangi, Peter; Okendo, Javan; Mogotsi, Milton; Ogunbayo, Ayodeji; Adelabu, Olusesan; Sondlane, Hlengiwe; Maotoana, Makgotso; Mahomed, Lutfiyya; Morobadi, Molefi Daniel; Vawda, Sabeehah; von Gottberg, Anne; Bhiman, Jinal; et al. (Frontiers in Virology, 2022)
Since the COVID-19 outbreak emerged, SARS-CoV-2 has continuously evolved into variants with underlying mutations associated with increased transmissibility, potential escape from neutralizing antibodies, and disease severity. The SARS-CoV-2 pandemic in South Africa has been characterized by periods of infections with four major epidemic waves. To determine whether the variants driving the epidemic waves at the national level were also driving the epidemic waves at the local level, we performed analysis of a total of 1287 samples from qPCR confirmed SARS-CoV-2 positive individuals. The samples were subjected to viral RNA extraction, genomic amplification, and sequencing. Variant assignment of the viral sequences and mutation identification were conducted using PANGOLIN and SARS-CoV-2 genome annotator, respectively. Our analysis revealed that during the initial part of the first wave, B.1, B.1.1, B.1.1.53, B.1.1.448 and B.1.237 circulated in the Free State province, followed by Beta variant, B.1.351 later in the wave. Although most of the initially detected variants disappeared during the second wave, the Beta variant, B.1.351, persisted. Early in the third wave, the Beta variant, B.1.351, predominated but was replaced by the Delta sub-lineage, AY.45. The fourth wave was characterized by unique emergence of the Omicron sub-variant, BA.1. The data further indicates that SARS-CoV-2 variants driving the epidemic waves in the Free State at the local level correlated with the ones driving the epidemic waves at the national level. Findings from this study highlight the importance of continued genomic surveillance and monitoring of the circulating SARS-CoV-2 variants to inform public health efforts and ensure adequate control of the ongoing pandemic.